Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Dinas Pendidikan Kabupaten Gianyar - Pioni, Kadek; Ayu Wimba, I Gusti; Suasti Puja, I Made (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
This study was conducted at the Gianyar District Education Office, with a population of 180 people and a sample of 64 people using slovin techniques and with the method of determining samples using simple random sampling. The instruments used in this study are validity tests and reliability tests, then use classical assumption tests and multiple linear regression analysis, determination, t test and f test. Based on the results of the study, transformational leadership had a positive and significant effect on employee performance in the Gianyar District Education Office where thitung value = 3,987 > ttabel = 1,999. Organizational culture has a positive and significant effect on employee performance in the Gianyar District Education Office where thitung value = 6,355 > ttabel = 1,999. Transformational leadership and organizational culture simultaneously positively and significantly affect employee performance in the Gianyar District Education Office where Fhitung obtained = 53,859 > Ftabel = 3.15. The advice that can be given is to foster mutual respect between fellow employees, leaders provide supportive motivation for all employees who work, and always provide direction for each employee so as to improve employee performance.This study was conducted at the Gianyar District Education Office, with a population of 180 people and a sample of 64 people using slovin techniques and with the method of determining samples using simple random sampling. The instruments used in this study are validity tests and reliability tests, then use classical assumption tests and multiple linear regression analysis, determination, t test and f test. Based on the results of the study, transformational leadership had a positive and significant effect on employee performance in the Gianyar District Education Office where thitung value = 3,987 > ttabel = 1,999. Organizational culture has a positive and significant effect on employee performance in the Gianyar District Education Office where thitung value = 6,355 > ttabel = 1,999. Transformational leadership and organizational culture simultaneously positively and significantly affect employee performance in the Gianyar District Education Office where Fhitung obtained = 53,859 > Ftabel = 3.15. The advice that can be given is to foster mutual respect between fellow employees, leaders provide supportive motivation for all employees who work, and always provide direction for each employee so as to improve employee performance.